Large uterine leiomyoma in a premenarchal 11-year-old patient: A case report - Rona Ding; Annie Galloway; Anne-Marie Amies Oelschlager; Katherine Debiec (Elsevier, 2023)
Introduction: Uterine leiomyomas, solid benign monoclonal tumors, are the most common pelvic tumor in women. Sex steroid hormones are thought to play a role in their pathogenesis, and they are known to increase with age in premenopausal women. Leiomyomas are exceedingly rare in the pediatric and adolescent population and even more so in premenarchal females. Case presentation: An 11-year-old premenarchal patient presented with a large abdominal mass, which had been increasing in size for the previous year. Laboratory studies were normal. Magnetic Resonance Imaging (MRI) confirmed a solid, circumscribed 8.5× 16.5 × 15.9 cm mass. Open biopsy was consistent leiomyoma. Exploratory laparotomy via infraumbilical vertical midline incision was performed. After exteriorizing the uterus, compressing the uterine arteries with a Penrose drain and injecting dilute vasopressin into the serosa of the uterus, the plane beneath the serosa, between the leiomyoma and normal myometrium was identified. The mass was completely resected without entering the endometrium. The uterus was closed transversely, from cornua to cornua in three layers. Menarche occurred 4 months after surgery. Three years post-operatively, the patient remains menstruating normally and free of recurrent leiomyoma. Conclusion: Though rare in premenarchal patients, leiomyoma should be considered in the differential for pelvic and uterine masses. An understanding of the surgical technique for uterine preservation is important. The underlying factors for stimulation of this large benign uterine mass remain unknown.